Fisheries school libraries in Southern Tagalog Region a survey with recommendations - Soriano, Rosalia F. (Institute of Library Science, University of the Philippines Diliman, 1981)
This survey aims to provide a comprehensive information base regarding fishery school libraries in the Southern Tagalog region during the school year 1980-81. There are nine fishery schools presently operating in Region IV; however, only seven libraries are included in this study.